Scale-integrated simulation of coupled radiation and convection in metal foam layer under high-flux irradiation. (April 2020) - Xia, Xin-lin; Li, Zhen-huan; Fan, Chao; Li, Xiao-lei; Sun, Chuang
Highlights: A scale-integrated strategy is presented for studying coupled radiation and convection inside metal foam. Absorbed radiative fluxes and re-radiation via Monte Carlo method are tightly coupled with CFD simulation. Fluctuated characteristics and overall heat transfer performance are simultaneously reflected. Significant reduction of computational effort is achieved in comparison with the discrete-scale simulation. Abstract: Coupled radiation-convection heat transfer inside a unit metal foam layer with high-flux irradiation is studied using improved scale-integrated simulation. It integrates the discrete-scale CFD simulation with that of continuum-scale via the multi-domain concept with thermal radiation effect considered. Conservations of mass flux and energy are satisfied on these specified subdomain interfaces, and a special defined transition zone with geometry-dependent functional quantities is introduced within the continuum-scale subdomain. This zone is adjacent to the discrete-scale subdomain which ensures a reasonable transition. Absorbed radiative fluxes and radiative heat transfer within the whole domain are calculated with Monte Carlo method and treated as heat sources. The problem under consideration has been investigated via the discrete-scale simulation, the continuum-scale simulation, and the scale-integrated simulation. The accurateness of scale-integrated simulation has been fully validated for predicting both flow field and heat transfer characteristics in comparison with the outcomes of discrete-scale simulation and other investigations. Deviations between the outcomes of continuum-scale simulation and discrete-scale simulation are found to be mainly caused by inconsistent local absorbed radiative heat fluxes distribution and impinging effect around the entry region. Up to 70% and 60% reduction of computation time and memory footprints are achieved when scale-integrated strategy is employed for the CFD simulation compared with the discrete-scale simulation. Meanwhile, the detailed fluctuated characteristics of the local concerned region and overall heat transfer performance can be precisely reflected. It may break up the computation limitations of the discrete-scale simulation in studying the energy transport process in foam based solar receiver applications.